CLASS OF THE LEADER SCHOOL PUBLIC ORGANIZATIONS WITH TAKE TO GO WORK - Mamarajabova Yulduz Chorshanbi qizi; Bobomurodov Sirojiddin (Journals Park Publishing, 2023)
In this article, the work of the class leader with public organizations of the school, the activity of the class leader in the system of educational work in the school is widely covered.
Keywords: Student, youth, leadership, activity, organization, methodology, education , forming a sense of duty, ideology , values , attitudes.